DEMOKRASI DAN GERAKAN SOSIAL (BAGAIMANA GERAKAN MAHASISWA TERHADAP DINAMIKA PERUBAHAN SOSIAL) - Idil Akbar (JWP (Jurnal Wacana Politik), 2016)
The inception of social groups nowadays believed as positive indication cultivation of democracy in some country, including Indonesia. The existence of social group aims to create a social change better and gratify the people interest. One of the social group is student movement that in any political event has become the pioneer for social change. This article aims to analyze how does democracy become important factor to a social movement, particularly student movement to an occurrence of social change in Indonesia. This research using a qualitative descriptive method to analyze how is social movement and democracy in Indonesia, especially related to student movement through to social change. As a result that student movement is the most important thing to realizing social change. As an agent of change, the idealism of student is valued indicator-weather social change has moved as well or perhaps full of political interest. The student movement also becomes indicator for sustainability of democracy.